PENGARUH REALISASI PENANAMAN MODAL DALAM NEGERI (PMDN) DAN REALISASI PENANAMAN MODAL ASING (PMA) TERHADAP KESEMPATAN KERJA KABUPATEN/KOTA DI KALIMANTAN BARAT - B01108026, Ratna Juliawati (Jurnal Pembangunan dan Pemerataan, 2013)
This study aimed to analyze the effect of the realization of domestic investment (DCI) and the realization of foreign investment (FDI) on employment in West Kalimantan. The method used is the model using regression analysis of panel data (cross section and time series) using the fixed effects approach. Observation data as much as 40 in 8 districts / cities in West Kalimantan during the period 2007 to 2011, the data processing computer program using E-views 6. The results of this study indicate that the realization of domestic investment (DCI) provide a negative and significant impact on employment in the district / town in West Kalimantan. Actual foreign direct investment (FDI) is positive but not significant effect on employment in the district/town in West Kalimantan. Keywords: Domestic Investment, Foreign Investment, Employment Opportunities